SPI2 T3SS effectors facilitate enterocyte apical to basolateral transmigration of Salmonella-containing vacuoles in vivo. (1st January 2021) - Fulde, Marcus; van Vorst, Kira; Zhang, Kaiyi; Westermann, Alexander J.; Busche, Tobias; Huei, Yong Chiun; Welitschanski, Katharina; Froh, Isabell; Pägelow, Dennis; Plendl, Johanna; Pfarrer, Christiane; Kalinowski, Jörn; et al.
ABSTRACT: Salmonella pathogenicity island (SPI) 2 type three secretion system (T3SS)-mediated effector molecules facilitate bacterial survival in phagocytes but their role in the intestinal epithelium in vivo remains ill-defined. Using our neonatal murine infection model in combination with SPI2 reporter technology and RNA-Seq of sorted primary enterocytes, we demonstrate expression of SPI2 effector molecules by intraepithelial Salmonella Typhimurium (S . Typhimurium). Contrary to expectation, immunostaining revealed that infection with SPI2 T3SS-mutants resulted in significantly enlarged intraepithelial Salmonella -containing vacuoles (SCV) with altered cellular positioning, suggesting impaired apical to basolateral transmigration. Also, infection with isogenic tagged S . Typhimurium strains revealed a reduced spread of intraepithelial SPI2 T3SS mutant S . Typhimurium to systemic body sites. These results suggest that SPI2 T3SS effector molecules contribute to enterocyte apical to basolateral transmigration of the SCV during the early stage of the infection.